The ability to maintain static balance in competitors of cyclic sports at the stage of directed training - Zurek, P.; Rynkiewicz, M.; Rynkiewicz, T.; Kos, H. (Studies in Physical Culture and Tourism, 2010)
The aim of the research was to determine the level of ability to maintain static balance in young competitors of cyclic sports as well as to reveal the influence of gender and body mass on the ability`s features. The study attempted to determine the range and direction of the ability to maintain static balance depending on the practiced sport. The study sample consisted of 114 kayakers, rowers, swimmers, cyclists and triathletes (28 girls and 86 boys) at the age of 16.0 ± 1.4. The ability to maintain static balance was determined by means of posturography in an erect position with eyes open. It was established that gender and body mass did not have a significant influence on the basic features of the ability to maintain static balance. Lack of statistically significant differences in the relationship between the ability to maintain static balance and the practiced sport was also found. Junior subjects manifested features of the ability to maintain static balance comparable to those of tennis players, whose game is dominated by acyclic and higher movements, as distinct from non-training subjects.